A population-based follow-up study shows high psychosis risk in women with PCOS - Karjula, Salla; Arffman, Riikka K.; Morin-Papunen, Laure; Franks, Stephen; Järvelin, Marjo-Riitta; Tapanainen, Juha S.; Miettunen, Jouko; Piltonen, Terhi T. (Archives of Women's Mental Health, 2023)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting up to 18% of women. Besides metabolic and fertility aspects, attention has lately been directed towards the detrimental effect of PCOS on psychological health. The objective of the study was to investigate whether women with PCOS are at higher risk for psychotic disorders. The study population derives from the Northern Finland Birth Cohort 1966 (N = 5889 women). The women with PCOS were identified by two simple questions on oligo-amenorrhea and hirsutism at age 31. Women reporting both symptoms were considered PCOS (N = 124) and asymptomatic women as controls (N = 2145). The diagnosis of psychosis was traced using multiple national registers up to the year 2016. Symptoms of psychopathology were identified using validated questionnaires at age 31. Women with PCOS showed an increased risk for any psychosis by age 50 (HR [95% CI] 2.99, [1.52-5.82]). Also, the risk for psychosis after age 31 was increased (HR 2.68 [1.21-5.92]). The results did not change after adjusting for parental history of psychosis, nor were they explained by body mass index or hyperandrogenism at adulthood. The scales of psychopathology differed between women with PCOS and non-PCOS controls showing more psychopathologies among the affected women. PCOS cases were found to be at a three-fold risk for psychosis, and they had increased psychopathological symptoms. PCOS should be taken into consideration when treating women in psychiatric care. More studies are required to further assess the relationship between PCOS and psychotic diseases. Peer reviewed